From Social Trust to Halal Industry Dynamic: The Synergy of Islamic Social Capital and Financial Capability in Small Enterprises Sectors - Afdawaiza, Afdawaiza; Yusfiarto, Rizaldi; Pambekti, Galuh Tri; Al Ghunaimi, Hisham; Febriyanto, Ahmad (Fakultas Syariah UINSI Samarinda, 2025)
This study aims to examine the determinants of performance in Halal micro, small, and medium enterprises (MSMEs) by positioning Islamic Social Capital (ISC) as the primary explanatory construct. To provide a more comprehensive framework, Islamic Financial Literacy (IFL) and Islamic Financial Inclusion (IFI) are integrated into the model to capture the knowledge and financial accessibility dimensions essential for Halal MSME development. A quantitative approach was employed, utilizing partial least squares structural equation modeling (PLS-SEM) on survey data from 242 Muslim-owned Halal MSMEs in Indonesia. The results reveal that ISC significantly enhances IFL, which in turn promotes IFI and ultimately strengthens MSME performance. These findings highlight the pivotal role of cohesive and ethically grounded social networks in facilitating financial literacy and access to Sharia-compliant financial services. The novelty of this study lies in integrating ISC with IFL and IFI within a single model, a relationship that has not been comprehensively explored in prior research. By bridging Islamic social capital with financial capability from an Islamic legal-ethical perspective, this study contributes new insights into how community-based mechanisms can drive the growth and resilience of Halal MSMEs.